Pengaruh Kemampuan Kerja, Disiplin Kerja dan Pelatihan Kerja Melalui Motivasi terhadap Prestasi Kerja Karyawan pada PT Kealyn Mandiri Sejahtera - Muhammad Oceano Fauzan (Universitas Batanghari, 2022)
In this study, the variables used were work ability, work discipline, job training, motivation and work performance for employees of PT Kealyn Mandiri Sejahtera. The purpose of this study is to provide input to PT Kealyn Mandiri Sejahtera and increase knowledge for readers. The research method used is by distributing questionnaires to employees of PT Kealyn Mandiri Sejahtera, in answering the questionnaire respondents simply mark the column containing the Likert's Scale (1 - 5) above it. The results obtained from this study, partially work ability on motivation has an insignificant negative effect, while work discipline has a positive and significant effect on motivation and job training on motivation has an insignificant negative effect, as well as the work ability variable on work performance has an insignificant negative effect, while work discipline has a positive and significant effect on work performance and job training on work performance has an insignificant negative effect, and the motivation variable on work performance partially has a positive and significant effect. Meanwhile, simultaneously work ability, work discipline and job training through motivation on work performance have a positive influence